ANALISIS PERBEDAAN HARGA DAN VOLUME PERDAGANGAN SAHAM PADA PERUSAHAAN INDEKS LQ45 DI BURSA EFEK INDONESIA SEBELUM DAN SAAT PANDEMI COVID-19 - Adawiyah, Siti; Fachhruddin, Rudy; Mahdi, Sayed; Saputra, Mulia (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
The Pandemic of COVID-19 has affected different areas of life, such as education, social, tourism and the economy. One of the economic instruments affected by the Pandemic is the capital market. The aim of this research was to look at stock prices and share trading volume in LQ45 index firms on the Indonesia Stock Exchange before and after the COVID-19 Pandemic. This type of research is a quantitative study with an event study approach. The data collected is the price and trading volume of shares of LQ45 index companies from December 03, 2019, to May 31, 2020. The results of this study indicate: (1) There are differences in stock prices in LQ45 index companies before and during the COVID-19 Pandemic. (2) There are differences in stock trading volume in LQ45 index companies before and during the COVID-19 Pandemic. These results indicate that the COVID-19 Pandemic has reacted on the capital market by influencing investors' decisions to sell their shares and resulting in a decline in stock prices.